6x-4y=96

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 6x from both sides of the equation.

-4y=96-6x

Divide each term by -4 and simplify.

Divide each term in -4y=96-6x by -4.

-4y-4=96-4+-6x-4

Cancel the common factor of -4.

Cancel the common factor.

-4y-4=96-4+-6x-4

Divide y by 1.

y=96-4+-6x-4

y=96-4+-6x-4

Simplify 96-4+-6x-4.

Simplify each term.

Divide 96 by -4.

y=-24+-6x-4

Cancel the common factor of -6 and -4.

Factor -2 out of -6x.

y=-24+-2(3x)-4

Cancel the common factors.

Factor -2 out of -4.

y=-24+-2(3x)-2(2)

Cancel the common factor.

y=-24+-2(3x)-2⋅2

Rewrite the expression.

y=-24+3×2

y=-24+3×2

y=-24+3×2

y=-24+3×2

Reorder -24 and 3×2.

y=3×2-24

y=3×2-24

y=3×2-24

Rewrite in slope-intercept form.

y=32x-24

y=32x-24

Using the slope-intercept form, the slope is 32.

m=32

Find the Slope 6x-4y=96